Development of solutions concerning regulation of proper deformations in alkali-activated cements - Krivenko, P.; Gots, V.; Petropavlovskyi, O.; Rudenko, I.; Konstantynovskyi, O.; Kovalchuk, A. (ПП «Технологічний Центр», 2019)
The essence of the problem related to proper deformations in alkali-activated cements (AAC) complicated with high content of gel-like hydrate formations was analyzed. Cement types diametrically opposite in their compositions and, accordingly, in the content of gel phases during hydration, that is, the alkali-acti- vated portland cement (AAPC) and alkali-activated slag cement (AASC) were taken for consideration. Approaches to formation of an effective structure of artificial stone counteracting shrinkage deformation by means of interference in structure formation when using complexes of mineral and organic compounds were proposed. Such compounds in composition of complex organomineral admixtures jointly influence intensification of crystallization processes and formation of an effective pore structure and morphology of hydrate phases while reducing water content in artificial stone. Salt electrolytes of various anionic types and anion-active surface-active substances were considered as ingredients of the proposed complex modifying admixtures. It has been found that the “salt electrolyte–surfactant” system is the most effective for AAPC modification. It was shown that modification of AAPC with this complex admixture based on NaNO3 reduced shrinkage from 0.406 to 0.017 mm/m. Instead, the use of Na2SO4 provided AAC of this type with a capacity of expansion up to 0.062 mm/m. It was shown that the effect of compensated shrinkage of modified AAPC is associated with a higher crystallization of low-basicity hydrosilicates (CSH(B)) and calcium hydroaluminates (CaO∙Al2O3∙10H2O). An additional effect is associated with formation of sulfate-containing sodium-calcium hydroaluminate (for the Na2SO4-based system) and crystalline calcium hydronitroaluminate (for the NaNO3-based system) with a corresponding microstructure stress. For further development, a complex admixture of “Portland cement clinker–salt electrolyte–surfactant” system was proposed for AASC modification. It provided shrinkage reduction from 0.984 mm/m to 0.683 mm/m. Minimization of the modified AASC shrinkage was explained by formation of sodium hydroalumosilicate of gmelinite type ((Na2Ca)∙Al2∙Si4∙O12∙6H2O) with a high degree of crystallization along with low-basicity calcium hydrosilicates. It was noted that the cement stone structure is characterized by high density, uniformity, and consolidation of hydrate formations.
Keywords: alkali-activated cement; salt electrolyte; complex organo-mineral admixture; structure formation; proper deformations; shrinkage; лужний цемент; сiль-електролiт; комп - лексна органо-мiнеральна добавка; структуроутворення; усадка; деформацiї; 691.5